Natural land carbon dioxide exchanges in the ECMWF integrated forecasting system: Implementation and offline validation. Issue 12 (17th June 2013) - Boussetta, Souhail; Balsamo, Gianpaolo; Beljaars, Anton; Panareda, Anna‐Agusti; Calvet, Jean‐Christophe; Jacobs, Cor; van den Hurk, Bart; Viterbo, Pedro; Lafont, Sebastien; Dutra, Emanuel; Jarlan, Lionel; Balzarolo, Manuela; et al.
Abstract: [1] The European Centre for Medium‐Range Weather Forecasts land surface model has been extended to include a carbon dioxide module. This relates photosynthesis to radiation, atmospheric carbon dioxide (CO2 ) concentration, soil moisture, and temperature. Furthermore, it has the option of deriving a canopy resistance from photosynthesis and providing it as a stomatal control to the transpiration formulation. Ecosystem respiration is based on empirical relations dependent on temperature, soil moisture, snow depth, and land use. The CO2 model is designed for the numerical weather prediction (NWP) environment where it benefits from good quality meteorological input (i.e., radiation, temperature, and soil moisture). This paper describes the CO2 model formulation and the way it is optimized making use of off‐line simulations for a full year of tower observations at 34 sites. The model is then evaluated against the same observations for a different year. A correlation coefficient of 0.65 is obtained between model simulations and observations based on 10 day averaged CO2 fluxes. For sensible and latent heat fluxes there is a correlation coefficient of 0.80. To study the impact on atmospheric CO2, coupled integrations are performed for the 2003 to 2008 period. The global atmospheric growth is well reproduced. The simulated interannual variability is shown to reproduce the observationally based estimates with a correlation coefficient of 0.70. The main conclusions are (i) the simple carbon dioxide model is highly suitable for the numerical weather prediction environment where environmental factors are controlled by data assimilation, (ii) the use of a carbon dioxide model for stomatal control has a positive impact on evapotranspiration, and (iii) even using a climatological leaf area index, the interannual variability of the global atmospheric CO2 budget is well reproduced due to the interannual variability in the meteorological forcing (i.e., radiation, precipitation, temperature, humidity, and soil moisture) despite the simplified or missing processes. This highlights the importance of meteorological forcing but also cautions the use of such a simple model for process attribution. Key Points: Land surface carbon fluxes modeling within a global NWP system Improved surface energy fluxes Better interannual variability of atmospheric CO2 growth